Identification of lignin genes and regulatory sequences involved in secondary cell wall formation in Acacia auriculiformis and Acacia mangium via de novo transcriptome sequencing - Cannon Charles H; Wong Melissa ML; Wickneswari Ratnam (BMC Genomics, 2011)
Abstract Background Acacia auriculiformis × Acacia mangium hybrids are commercially important trees for the timber and pulp industry in Southeast Asia. Increasing pulp yield while reducing pulping costs are major objectives of tree breeding programs. The general monolignol biosynthesis and secondary cell wall formation pathways are well-characterized but genes in these pathways are poorly characterized in Acacia hybrids. RNA-seq on short-read platforms is a rapid approach for obtaining comprehensive transcriptomic data and to discover informative sequence variants. Results We sequenced transcriptomes of A. auriculiformis and A. mangium from non-normalized cDNA libraries synthesized from pooled young stem and inner bark tissues using paired-end libraries and a single lane of an Illumina GAII machine. De novo assembly produced a total of 42,217 and 35,759 contigs with an average length of 496 bp and 498 bp for A. auriculiformis and A. mangium respectively. The assemblies of A. auriculiformis and A. mangium had a total length of 21,022,649 bp and 17,838,260 bp, respectively, with the largest contig 15,262 bp long. We detected all ten monolignol biosynthetic genes using Blastx and further analysis revealed 18 lignin isoforms for each species. We also identified five contigs homologous to R2R3-MYB proteins in other plant species that are involved in transcriptional regulation of secondary cell wall formation and lignin deposition. We searched the contigs against public microRNA database and predicted the stem-loop structures of six highly conserved microRNA families (miR319, miR396, miR160, miR172, miR162 and miR168) and one legume-specific family (miR2086). Three microRNA target genes were predicted to be involved in wood formation and flavonoid biosynthesis. By using the assemblies as a reference, we discovered 16,648 and 9,335 high quality putative Single Nucleotide Polymorphisms (SNPs) in the transcriptomes of A. auriculiformis and A. mangium, respectively, thus yielding useful markers for population genetics studies and marker-assisted selection. Conclusion We have produced the first comprehensive transcriptome-wide analysis in A. auriculiformis and A. mangium using de novo assembly techniques. Our high quality and comprehensive assemblies allowed the identification of many genes in the lignin biosynthesis and secondary cell wall formation in Acacia hybrids. Our results demonstrated that Next Generation Sequencing is a cost-effective method for gene discovery, identification of regulatory sequences, and informative markers in a non-model plant.